Frailty index as a biomarker of lifespan and healthspan: focus on pharmacological interventions - Palliyaguru, Dushani L. (Mech Ageing Dev, 2019)
Although survival has been the focus of aging research for many years, the field is rapidly evolving towards incorporating healthspan and health indices in studies that explore aging-related outcomes. Frailty is one such measure that is tightly correlated with human aging. Several frailty measures have been developed that focus on phenotypes of aging, including physical, cognitive and metabolic health that define healthspan. The extent at which cumulative deficits associated with frailty predict functional characteristics of healthy aging and longevity is currently unknown. A growing consensus for the use of animal models has emerged to evaluate a composite measure of frailty that provides a translational basis to understanding human frailty. In this review, we will focus on the impact of several anti-aging interventions, some of which have been characterized as caloric restriction (CR) mimetics such as metformin, rapamycin, resveratrol as well as more novel approaches that are emerging in the field - nicotinamide adenine dinucleotide precursors, small molecule activators of sirtuins, and senolytics - on a number of frailty measurements associated with aging-related outcomes in mice and discuss the translatability of such measures to human frailty.